A 5 YEAR STUDY OF UNNATURAL CHILDHOOD DEATHS IN IMPHAL FROM 2009-2013 (Journal of Forensic Medicine & Toxicology, 2015)
Injury & Violence are major killers of children and adolescents under the age of 18 years throughout the world, and are responsible for about 950000 deaths each year. Unnatural childhood deaths are not only sad, but also involve a sense of deep remorse blaming oneself for the inability to protect one’s children from harm. Out of the 1879 post-mortem examinations done during the period, 2009-2013, at the Morgue of Regional Institute of Medical Sciences, Imphal, 2.34%, i.e., 44 cases were paediatric cases. The purposes of this study were to report the autopsy findings of unnatural childhood deaths, and to identify the prevalence of specific factors such as age and sex distribution, postmortem findings, cause of death, manner of death, seasonal variation, the various types of accidental and homicidal deaths, rural-urban distribution, age-group prevalence of the manner and types of death and to analyze and compare the findings with studies from other parts of the world. Children up to 12 years of age were studied. Majority of the cases were accidental in nature with road traffic accident being the cause. Since most of these deaths are preventable, a thorough analysis of the causes will help in formulating preventive guidelines.
Keywords: Pediatric autopsy; Unnatural childhood deaths; Cause of death; Manner of death